Acute Myeloid Leukemia Chemo-Resistance Is Mediated by E-selectin Receptor CD162 in Bone Marrow Niches - Erbani, Johanna; Tay, Joshua; Barbier, Valerie; Levesque, Jean-Pierre; Winkler, Ingrid G. (Frontiers in Cell and Developmental Biology, 2020)
The interactions of leukemia cells with the bone marrow (BM) microenvironment is critical for disease progression and resistance to treatment. We have recently found that the vascular adhesion molecule E-(endothelial)-selectin is a key niche component that directly mediates acute myeloid leukemia (AML) chemo-resistance, revealing E-selectin as a promising therapeutic target. To understand how E-selectin promotes AML survival, we investigated the potential receptors on AML cells involved in E-selectin-mediated chemo-resistance. Using CRISPR-Cas9 gene editing to selectively suppress canonical E-selectin receptors CD44 or P-selectin glycoprotein ligand-1 (PSGL-1/ CD162) from human AML cell line KG1a, we show that CD162, but not CD44, is necessary for E-selectin-mediated chemo-resistance in vitro. Using preclinical models of murine AML, we then demonstrate that absence of CD162 on AML cell surface leads to a significant delay in the onset of leukemia and a significant increase in sensitivity to chemotherapy in vivo associated with a more rapid in vivo proliferation compared to wild-type AML and a lower BM retention. Together, these data reveal for the first time that CD162 is a key AML cell surface receptor involved in AML progression, BM retention and chemo-resistance. These findings highlight specific blockade of AML cell surface CD162 as a potential novel niche-based strategy to improve the efficacy of AML therapy.